2012
DOI: 10.1111/j.1461-0248.2012.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of aboveground–belowground interactions

Abstract: Root herbivory can greatly affect the performance of aboveground insects via changes in plant chemistry. These interactions have been studied extensively in experiments where aboveground and belowground insects were feeding on the same plant. However, little is known about how aboveground and belowground organisms interact when they feed on plant individuals that grow after each other in the same soil. We show that feeding by aboveground and belowground insect herbivores on ragwort (Jacobaea vulgaris) plants e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
165
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(181 citation statements)
references
References 47 publications
(85 reference statements)
4
165
3
1
Order By: Relevance
“…It was recently discovered that belowground hyphal networks of arbuscular mycorrhizal fungi act as a conduit for defence signals from plants attacked by herbivorous insects to adjacent non-attacked plants, thereby acting as an early warning system for herbivore attack 75 . Also, foliar and shoot herbivory has been shown to exert a unique soil legacy effect which greatly influences the production of defence chemicals in succeeding plants, and that this legacy effect is mediated by alterations in soil fungal community composition 76 . These studies illustrate that soil biota can impact plant growth by modifying biotic interactions between plants and their natural enemies, but the role of soil biodiversity in these processes remains unresolved.…”
Section: Soil Biodiversity and Community Dynamicsmentioning
confidence: 99%
“…It was recently discovered that belowground hyphal networks of arbuscular mycorrhizal fungi act as a conduit for defence signals from plants attacked by herbivorous insects to adjacent non-attacked plants, thereby acting as an early warning system for herbivore attack 75 . Also, foliar and shoot herbivory has been shown to exert a unique soil legacy effect which greatly influences the production of defence chemicals in succeeding plants, and that this legacy effect is mediated by alterations in soil fungal community composition 76 . These studies illustrate that soil biota can impact plant growth by modifying biotic interactions between plants and their natural enemies, but the role of soil biodiversity in these processes remains unresolved.…”
Section: Soil Biodiversity and Community Dynamicsmentioning
confidence: 99%
“…Herbivores also modulate microbial behavior and community structure through regulating plant physiology and defense systems (Gehring and Bennett, 2009; Lakshmanan et al, 2012; Tack and Dicke, 2013). The belowground herbivorous insect Agriotes lineatus L. negatively affects the composition of fungal communities in the ragwort ( Jacobaea vulgaris ) rhizosphere (Kostenko et al, 2012). More specifically, infestation by the belowground insect wireworm ( Agriotes lineatus L.) leads to the accumulation of the major plant defense compounds pyrrolizidine alkaloids in ragwort plants and reduces the levels of the pathogenic fungus Fusarium oxysporum in roots (Bezemer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has become evident that such changes in soil microbial communities, via plant-mediated processes, can affect the performance of aboveground organisms that interact with these plants. For example, several greenhouse studies have shown that soil legacy effects, the effects of earlier plant growth on the microbial community in the soil, can have strong effects on aboveground herbivores feeding on later growing conspecific plants in those soils (Kostenko et al, 2012;Kos et al, 2015). A recent study, for example, revealed that soil legacies left by grasses and forbs have contrasting effects on a chewing herbivore that fed on plant communities growing on soils with these legacies (Heinen et al, 2018).…”
Section: Plant-soil Feedback Effects On Plant-insect Interactions In mentioning
confidence: 99%
“…Such speciesspecific microbial profiles can influence the performance of other plants that grow later in the same soil (Kostenko et al, 2012;Bezemer et al, 2013;Kos et al, 2015;Heinen et al, 2018). This process is known as plant-soil feedback and can be an important driver of plant community dynamics (Kardol et al, 2006).…”
Section: Plant-soil Feedback Effects On Plant-insect Interactions In mentioning
confidence: 99%